2004
DOI: 10.1161/01.cir.0000129233.51320.92
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Recovery From End-Stage Heart Failure Using Left-Ventricular Assist Device and Pharmacological Therapy Correlates With Increased Sarcoplasmic Reticulum Calcium Content but Not With Regression of Cellular Hypertrophy

Abstract: Background-Left ventricular assist device (LVAD) treatment is known to lead to structural and functional cellular modifications in the heart. The relevance of these changes for clinical recovery is unknown. Methods and Results-We compared properties of cardiomyocytes obtained from tissue taken at explantation of the LVAD in patients with clinical recovery with those obtained from hearts of patients who did not show clinical recovery, thus requiring transplantation. Compared with myocytes taken at implantation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(98 citation statements)
references
References 19 publications
1
96
0
1
Order By: Relevance
“…[1][2][3] This normalization of diastolic properties results from a regression of myocyte hypertrophy, including reduced LV mass, wall thickness, and myocyte diameter. 4,5 In addition, LVAD support has been associated with a trend toward normalization in cardiomyocyte function, 6 calcium cycling properties, 7 and expression of various genes. 8 In addition to changes in intrinsic myocardial properties, LVAD use is associated with changes in the characteristics and metabolism of the extracellular matrix (ECM).…”
mentioning
confidence: 99%
“…[1][2][3] This normalization of diastolic properties results from a regression of myocyte hypertrophy, including reduced LV mass, wall thickness, and myocyte diameter. 4,5 In addition, LVAD support has been associated with a trend toward normalization in cardiomyocyte function, 6 calcium cycling properties, 7 and expression of various genes. 8 In addition to changes in intrinsic myocardial properties, LVAD use is associated with changes in the characteristics and metabolism of the extracellular matrix (ECM).…”
mentioning
confidence: 99%
“…Terracciano and co-workers have demonstrated that clinical recovery from terminal CHF after pharmacological and mechanical support is associated with modifications in excitation-contraction coupling, and sarcoplasmatic Ca 2+ homeostasis in particular, and not with a reduction of cardiomyocyte cell size. These findings underscore the importance of Ca 2+ cycling in CHF and its treatment [53].…”
Section: Ca 2+ Homeostasismentioning
confidence: 55%
“…In studies on transplanted human hearts, previous ␤-blockade restored the RyR function, phosphorylation, and levels of the binding proteins toward reference, with improved myocardial compliance and response to isoproterenol. 16 These studies do not explain why the ARB valsartan can restore the function of the ryanodine receptor and normalize the calcium leak from the SR without improving resting cardiac function. 17 The abnormalities of intracellular cardiac calcium kinetics in heart failure could equally well lie in defective uptake of calcium into the SR by the sarcoplasmic-endoplasmic reticulum calciumuptake pump (SERCA) and, more specifically, the cardiac isoform SERCA2a.…”
Section: Hyperadrenergic Signaling In Heart Failurementioning
confidence: 93%